2017
DOI: 10.1002/smll.201700035
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Iron's Attractive Chemical and Magnetic Properties in Microrocket Design, Extended Motion, and Unique Performance

Abstract: All‐in‐one material for microrocket propulsion featuring acid‐based bubble generation and magnetic guidance is presented. Electrochemically deposited iron serves as both a propellant, toward highly efficient self‐propulsion in acidic environments, and as a magnetic component enabling complete motion control. The new microrockets display longer lifetime and higher propulsion efficiency compared to previously reported active metal zinc‐based microrockets due to the chemical properties of iron and the unique stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 35 publications
0
28
0
Order By: Relevance
“…For instance, the use of dual stimuli offers multiple practical solutions to precisely guide nanomotors through a hybrid trigger. Chemically and physically propelled nanomotors have been integrated with diverse ferromagnetic segments (Ni, Fe, and Co) to establish control over the nanomotor directionality, by aligning them with a magnetic field or via magnetic torque applied to the motor structure . Such magnetic fields can be produced by a magnetic bar which offers direct manipulation or with a Helmholtz coil that produces a highly accurate 3D control.…”
Section: Multistimuli‐enabled Advanced Motion Controlmentioning
confidence: 99%
“…For instance, the use of dual stimuli offers multiple practical solutions to precisely guide nanomotors through a hybrid trigger. Chemically and physically propelled nanomotors have been integrated with diverse ferromagnetic segments (Ni, Fe, and Co) to establish control over the nanomotor directionality, by aligning them with a magnetic field or via magnetic torque applied to the motor structure . Such magnetic fields can be produced by a magnetic bar which offers direct manipulation or with a Helmholtz coil that produces a highly accurate 3D control.…”
Section: Multistimuli‐enabled Advanced Motion Controlmentioning
confidence: 99%
“…The Fe‐NP aggregates submerged in an aqueous solution of 3.38 wt% citric acid and 1% SDS moved with a speed of 7–20 µm s −1 . The electrodeposited multilayered PEDOT/Au/Fe‐based micromotors propelled by reaction with 1.2 m HCl to the speed of ≈35 µm s −1 . The chemical reaction involved is represented as Fe(s) + 2H 3 O + → Fe 2+ (aq) + 2H 2 O + H 2 (g).…”
Section: Catalytic Materials For Mnmsmentioning
confidence: 99%
“…Later, Solovev et al found that an incorporated ferromagnetic layer in rolled-up microtubes can be used to control the motion of microjet engines with magnetic fields [ 137 ]. Subsequently, magnetic control of microjets was improved [ 138 , 139 , 140 ] as well as other NMs including nanowire motors [ 141 ], Janus particles [ 142 , 143 ], paperbots [ 144 ], liquibots [ 145 ], freestyle nanoswimmer [ 146 ], fish-like nanoswimmers [ 147 ], liquid metal motors [ 148 ], flexible and linked superparamagnetic colloidal chains [ 149 ], chemo-magnetic structures [ 150 ], magneto-electric structures [ 151 ], magneto-acoustic structures [ 152 ] and chiral nanomagnets [ 153 ]. Fuel free NMs have advantages in biomedical applications, since there are no reaction products produced during the navigation [ 154 ].…”
Section: Motion Control and Externally Powered Micromotorsmentioning
confidence: 99%